2020
DOI: 10.1055/s-0040-1721796
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Menopause and Primary Ovarian Insufficiency: Time for a Paradigm Shift?

Abstract: This review summarizes the existing information concerning the genetic background of menopause and primary ovarian insufficiency (POI). There is overwhelming evidence that majority of genes are involved in double-strand break repair, mismatch repair, and base excision repair. The remaining loci were involved in cell energy metabolism and immune response. Gradual (or in case of rapid POI) accumulation of unrepaired DNA damage causes (premature) cell death and cellular senescence. This in turn leads to exhaustio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 52 publications
1
10
0
2
Order By: Relevance
“…Reproductive senescence, which menopause actually is, is also dependent on multiple intrinsic genetic factors. Reproductive ageing is not isolated from the overall somatic ageing process, and several studies strongly support the link between an early age of menopause and morbidity and mortality (Laven, 2020).…”
Section: Genetics Of Menopausementioning
confidence: 99%
See 3 more Smart Citations
“…Reproductive senescence, which menopause actually is, is also dependent on multiple intrinsic genetic factors. Reproductive ageing is not isolated from the overall somatic ageing process, and several studies strongly support the link between an early age of menopause and morbidity and mortality (Laven, 2020).…”
Section: Genetics Of Menopausementioning
confidence: 99%
“…Moreover, ageing oocytes seem to lose protective mechanisms against reactive oxygen species (ROS), giving rise to increased DNA damage (TABLE 1). Hence, accumulated ROS activity and increased vulnerability of oocytes to ROS lead to spindle instability, chromosomal abnormalities, telomere shortening and reduced developmental competence of aged oocytes (Laven, 2020). Last but not least there was an extensive overlap between the genetic variants associated with menopausal age and neurodegenerative and cardiovascular disease (CVD) as well as with diabetes mellitus (Ruth et al, 2021).…”
Section: Genetics Of Menopausementioning
confidence: 99%
See 2 more Smart Citations
“…It remains to be determined whether the prediction of age at menopause, albeit with a range spanning several years, may ultimately be feasible in this group of women facing reproductive decisions at a relatively early age. Of note, AMH levels are reduced in girls with newly diagnosed cancer even before the cancer treatment has started and it is suggested that possibly in relation to this impaired DNA repair mechanisms are involved that also seem in part to be involved in determination of age at menopause (31)(32)(33).…”
Section: Iatrogenic Ovarian Reserve Impairmentmentioning
confidence: 99%